Treatment of Anti-Factor VIII Antibodies - Blatt, Philip M.; White, Gilbert C., II; McMillan, Campbell W.; Roberts, Harold R. (Thrombosis and Haemostasis, 1977)
Bleeding episodes in patients with hemophilia A with anti-factor VIII antibodies are frequently difficult to treat. Factor VIII concentrates administered by continuous infusion or prothrombin complex concentrates (PCC) have been used for treatment. Hemophilia A patients with inhibitors who respond to factor VIII concentrates generally have low to moderate inhibitor titers (generally less than 20 Bethesda units). Those patients who receive PCC are quite difficult to evaluate but promising clinical responses have clearly been observed. This paper describes our experience with both modalities of therapy and will offer specific guidelines for such therapy.